Proceedings - 32. Workshop Computational Intelligence: Berlin, 1. - 2. Dezember 2022 - Schulte, Horst; Hoffmann, Frank; Mikut, Ralf (KIT Scientific Publishing, 2022)
This conference volume contains the contributions of the 32nd workshop "Computational Intelligence" of the Technical Committee 5.14 of the VDI/VDE Society for Measurement and Automation Technology (GMA) of 1.12. - 2.12.2022 in Berlin. The focus is on methods, applications and tools for.